The Impact of Financial Literacy on Financial Risk Tolerance: Mediating Role of Financial Behavior - Norwazli, Abdul Wahab; Bunyamin, Mubarokah (GBMR, 2023)
Financial risk tolerance (FRT) is reported to have impact on one’s financial decision. Increased risk tolerance while investing in assets is reportedly another key factor in enticing investors to take advantage of market possibilities. Findings from previous studies agreed that age and income level are among the factors that influence an individual’s FRT. This research intends to identify the influence of financial literacy on FRT with the mediating role of financial behavior among Malaysian investors. Primary data was analyzed involving 148 investors among working adults. To analyze the collected data, this research applied Partial Least Squares Structural Equation Model (PLS-SEM) by employing the software SmartPLS 3. Results revealed that financial literacy has a positive influence on financial behavior, and financial behavior has a positive impact of FRT. Additionally, findings indicated that financial behavior mediates the relationship between financial literacy with FRT. These findings contribute to the awareness of financial literacy, financial behavior, and FRT importance in making effective financial decisions. This study also will be useful for government and regulators to develop financial education and training programs among investors.